The Role of Safety Leadership in the Influence of Safety Coaching and Safety Engagement on Safety Performance - Hermawan, Febrian; Setyawan, Agustinus; Sudhartio, Lily (Jayapangus Press, 2024)
Occupational safety and health professionals play an important role in improving workplace safety. However, the effectiveness of safety leadership, safety coaching and engagement in improving safety performance, mediated by safety culture, remains under-researched. This study aims to analyze how these factors influence safety performance among occupational safety and health professionals in Riau Islands Province, Indonesia. This study used a structural equation modelling (SEM) approach for hypothesis testing based on data collected from 180 active occupational safety and health professionals using purposive sampling. The results showed that all hypotheses were supported: safety leadership mediated the relationship between safety training and safety engagement with safety performance. This suggests that leadership is important in fostering a safety culture and encouraging proactive employee engagement. In addition, safety training was found to significantly influence leadership and safety performance. The results of this study conclude that strengthening leadership and engagement in safety through targeted coaching and training can significantly improve safety outcomes in high-risk industries. The findings underscore the importance of integrating safety leadership and culture into organizational practices. Future research should explore the long-term impact of safety leadership interventions and the potential for cross-industry application to further improve workplace safety standards.